Study into the tourist attractiveness of Lubuskie Province municipalities using the aggregate measure - Szczuciński, P. (BUKETOV BUSINESS REVIEW, 2020)
Object: A special feature of contemporary economy is that processes occurring within it are characterised by growing dynamics and spatial diversification. One of the important phenomena in the development of each region or municipality is the tourist traffic taking place in their territory. Benefits associated with it include: improvement of living standards, increase in demand and income, reduced unemployment rate, development of infrastructure, sustenance of local crafts. Tourism is thus becoming an important way to revive the regional and local economy. Methods: In this paper, the Lubuskie Province was subjected to statistical research in this respect. Findings: A general characteristic of tourism development in the region was prepared and an attempt was made to assess the tourist attractiveness of municipalities using an aggregate measure with the median value. Conclusions: The ranking of municipalities obtained on the basis of this measure was compared with the rankings obtained for other commonly used aggregate measures. The study accounts for data obtained from various sources for the year 2018.